Assessing the contributions of climate change and human activities to cropland productivity by means of remote sensing. Issue 5 (3rd March 2020) - Yan, Yuchao; Xu, Xiaocong; Liu, Xiaoping; Wen, Youyue; Ou, Jinpei
ABSTRACT: It is essential for quantitatively assessing the influences of climate change (CC) and human activities (HA) on cropland productivity to clarify the associated drive mechanisms. However, few studies have quantitatively evaluated their relative contributions to cropland productivity in China. In this study, net primary productivity (NPP) was chosen as an indicator of cropland productivity. The actual NPP (ANPP) represents the combined effects of CC and HA on cropland productivity, and the potential NPP (PNPP) represents the effect of CC on cropland productivity. The difference between the actual and the potential NPP (HNPP) represents the effect of HA on cropland productivity. Meanwhile, we designed six scenarios to quantify the contributions of CC and HA to the inter-annual variation in ANPP. Our results showed that cropland ANPP in China as a whole increased at a rate of 3.68 g C m −2 year −1 ( p < 0.01) between 2000 and 2015. The contributions of CC and HA to the variations in cropland ANPP were 3.23 g C m −2 year −1 ( p < 0.01) and 0.45 g C m −2 year −1 ( p > 0.1), respectively. Furthermore, we found that 79.43% of total cropland area showed an inter-annual increase in ANPP, in which 56.22% of cropland area with increase in ANPP was predominantly influenced by CC, compared to 43.78% predominantly influenced by HA. Conversely, 20.57% of total cropland area showed an inter-annual decrease in ANPP, with 70.62% of cropland area with decrease in ANPP being predominantly influenced by HA compared with only 29.38% predominantly influenced by CC. Overall, CC was the dominant factor affecting increase in cropland ANPP, whereas HA was the dominant factor affecting decrease in cropland ANPP. We conclude that effective measures for protecting cropland resources need to be further strengthened, despite CC primarily promoting cropland ANPP.